Rìšti tipo veiksmažodžių esamojo laiko morfologinė struktūra - Kaukienė, Audronė (Baltistica, 1994)
THE MORPHOLOGICAL PRESENT TENSE STRUCTURE OF rìša TYPE VERBS The verbs of the type rìša in Lithuanian and Latvian dialects or in other indoeuropean languages have many parallel-forms of different morphological structures. Beside the forms with zero-formant one also can find infix- and the n, i̯ suffix-fоrms. Ancient, protoindoeuropean, can be those of the structure CeiC-ø or CeC-ø (zero-formant) and Ci-n-C or CiC-n (nasal infix or suffix-formants). They had been used without semantic difference (usually active). In East Baltic this system has changed. New verbal types appeared by the unification of the root vowel and semantic differentiation: a) the new verbs with the structure CeiC-ia, CieC-ia or CeC-ia (ia-stern), CIС-a (a-stem) and the relics of ancient infixial verbs become (or preserve) the active (causative) meaning (e. g. kneĩbia, kniẽbia, knìba, knim̃ba „sticks”, kreĩkia, kriẽkia, krìka „spreads”), b) the new infixial (or sta-stem) verbs acquire the mutative (resultative) meaning (e. g. knim̃ba „bows”, kriñka „brakes up”).